The other side of protest music: the Extreme Right and Skinhead Culture in democratic Portugal (1974-2015) - Marchi, R.; Zúquete, J. (JOMEC Journal, 2016)
Although Portugal does not have a significant radical right presence in its party system, in the last decades the country did witness the development of a neo-Nazi skinhead movement that expresses its white nationalist nature and goals through the musical genres of Rock Against Communism (RAC) and the related Oi!. Utilizing various historical sources and theoretical analysis, this study contextualizes the development of nationalist music in Portugal, both before and especially during the democratic period (1974-2015). It focuses on its protagonists, domestic and international networks, as well as on the few attempts to establish a common cause with radical right-wing political parties at the turn of the century and in present times.